Comparison of Deaf Children's Ability to Write Texts, Procedures, and Implementing Procedures for Cooking Instant Noodles - Rizki Cahya Iskandar; Budi Susetyo (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to reveal the differences in the abilities of deaf children in writing procedural texts and carrying out daily procedures. No study has been found that specifically compares deaf children's abilities to write procedural texts and to carry out procedures directly, especially in the Indonesian context. This study uses a descriptive, quantitative approach and involves 10 deaf students aged 12 to 18 years at the Tarbiyatul Mutaalimin Pagaden Special School, Subang. Data were collected using two instruments: a test of writing procedural texts on how to cook instant noodles and direct observation of the cooking process. Data from the writing test and practical observation will be compared to identify significant differences between the two abilities. A paired t-test was performed in SPSS to compare procedural text writing test scores with procedural practice observation scores. The results showed that deaf children's ability to write procedural texts was lower than their ability to carry out daily procedures. The average score for the procedural writing test was 47 out of 100, while the procedural practice observation showed an average score of 79.6 out of 100. Limitations influenced this difference in the use of appropriate language, limited vocabulary, and difficulty constructing logical, structured sentences.